Teachers' practices in encouraging self directedness in learning English as a second language - Abd. Samad, Arshad; Jasiran Awang, Hazel Adria; Nor Mohamad, Alif Fairus; Palpanaban, Sangeetha (Universiti Putra Malaysia Press, 2019)
The development of self-directed language learning needs to be seen not only from the point of view of the learners, but also from the perspective of the teachers. Teachers play a critical role in encouraging self-directedness and it is important to examine how they may or may not, either directly or indirectly, create opportunities to encourage self-directedness amongst their students. Although many teachers acknowledge the benefits of self-directedness, lessons in the classroom still tend to be teacher-centered. In this study, several English language teachers at a public tertiary level institution were observed over a period of two weeks to determine the extent they used techniques that encourage self-directedness. An observation checklist based on the four stages of the Staged levels of Self-Directedness model was used. Instances of when self-directedness was supported were also noted together with when opportunities to do so were missed. It was generally found that although practices that encouraged self-directedness were observed, teachers often missed opportunities to do so in the classroom. There were also few instances of practices that reflected the higher levels in Grow’s model, indicating that teachers were either hesitant or unable to practise student self-directedness in the classrooms.